Chikki: Food from De-oiled Peanut Cake - TYAGI, ARUN K; SHAH, N G; Vinjamur, M (Journal of Agricultural Engineering, 2012)
A â€œTel-Ghaniâ€ (Indian traditional oil-expression unit) of about 150 kg/day of peanuts, yields about 5% less oil from peanuts than mechanical oil expeller, and is an important entrepreneurial activity in villages. De-oiled cake fetch low price as animal feed. Use of peanut cake in snack food as chikki was attempted for value addition to improve the economics of the Tel-Ghani. Preparation of the snack, technical specifications of processes involved, characterization of the snack in terms of colour, texture, and sorption isotherms to predict keeping quality and economic analysis are reported. Chikki made from ground deolied cakepowder containing 16.3 % residual oil and having added 20% jaggery, 12% sugar, 8% liquid glucose and 4% vanaspati ghee scored best in sensory evaluation. The product - chikki not only provides a protein-rich food, but also improves the economics of Tel-Ghani.